2019
DOI: 10.1155/2019/2131467
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Scaffolds of Poly(ε-caprolactone)/Biosilicate® Biocomposites Prepared by Generative Manufacturing Process

Abstract: Scaffolds of poly(ε-caprolactone) (PCL) and their biocomposites with 0, 1, 3, and 5 wt.% Biosilicate® were fabricated by the generative manufacturing process coupled with a vertical miniscrew extrusion head to application for restoration of bone tissue. Their morphological characterization indicated the designed 0°/90° architecture range of pore sizes and their interconnectivity is feasible for tissue engineering applications. Mechanical compression tests revealed an up to 57% increase in the stiffness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…84 da Cunha 2019 fabricated PCL-Biosilicate scaffold using extrusion printer, with 0°/90°pore sizes and pore interconnectivity, which led to 57% increase in the stiffness of scaffold, without increasing any toxicity. 85 González-Gil (2019) used a bone nonunion model in Sprague-Dawley rats in six groups: control, live bone allograft, rhBMP-2 in collagen; acellular PCL; PCL with periosteumderived MSCs, and PCL containing bone marrow-derived MSCs. Significant new bone formation was seen in LBA, CS BMP2 and PCL PMSCs groups at 8 weeks.…”
Section: Cellular Bioactivity On Pcl Scaffoldsmentioning
confidence: 99%
“…84 da Cunha 2019 fabricated PCL-Biosilicate scaffold using extrusion printer, with 0°/90°pore sizes and pore interconnectivity, which led to 57% increase in the stiffness of scaffold, without increasing any toxicity. 85 González-Gil (2019) used a bone nonunion model in Sprague-Dawley rats in six groups: control, live bone allograft, rhBMP-2 in collagen; acellular PCL; PCL with periosteumderived MSCs, and PCL containing bone marrow-derived MSCs. Significant new bone formation was seen in LBA, CS BMP2 and PCL PMSCs groups at 8 weeks.…”
Section: Cellular Bioactivity On Pcl Scaffoldsmentioning
confidence: 99%
“…However, it is necessary to modify the filament to produce scaffolds for bone tissue regeneration using this technique. Cunha et al [14] produced 3D scaffolds of PCL/Biosilicate ® and the observed improvement in the mechanical properties and the addition of Biosilicate ® provided a good environment for cell attachment and proliferation [14]. It is worth noticing that the printed scaffold used a specific printing setup where the two separated materials were feed in powder form which may lead to some drawbacks as poor filler dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…It can be obtained a filament that forms a 3D scaffold geometry laid up on a platform [25]. Few studies [26,27] report its efficiency in tissue engineering manufacture. Dávila et al [26] and Cunha et al [27] studied the fabrication of polymer-ceramic scaffolds and reported the formation of undesirable ceramic aggregates in the polymeric matrix, which can be improved by adjusting the operational parameters during the manufacturing process, or applying a pre-process.…”
Section: Introductionmentioning
confidence: 99%